Sustained endocrine profiles of a girl with WAGR syndrome - Yui Takada; Yasunari Sakai; Yuki Matsushita; Kazuhiro Ohkubo; Yuhki Koga; Satoshi Akamine; Michiko Torio; Yoshito Ishizaki; Masafumi Sanefuji; Hiroyuki Torisu; Chad A. Shaw; Masayo Kagami; et al. (BMC, 2017)
Abstract Background Wilms tumor, aniridia, genitourinary anomalies and mental retardation (WAGR) syndrome is a rare genetic disorder caused by heterozygous deletions of WT1 and PAX6 at chromosome 11p13. Deletion of BDNF is known eto be associated with hyperphagia and obesity in both humans and animal models; however, neuroendocrine and epigenetic profiles of individuals with WAGR syndrome remain to be determined. Case presentation We report a 5-year-old girl with the typical phenotype of WAGR syndrome. She showed profound delays in physical growth, motor and cognitive development without signs of obesity. Array comparative genome hybridization (CGH) revealed that she carried a 14.4 Mb deletion at 11p14.3p12, encompassing the WT1, PAX6 and BDNF genes. She experienced recurrent hypoglycemic episodes at 5 years of age. Insulin tolerance and hormonal loading tests showed normal hypothalamic responses to the hypoglycemic condition and other stimulations. Methylation analysis for freshly prepared DNA from peripheral lymphocytes using the pyro-sequencing-based system showed normal patterns of methylation at known imprinting control regions. Conclusions Children with WAGR syndrome may manifest profound delay in postnatal growth through unknown mechanisms. Epigenetic factors and growth-associated genes in WAGR syndrome remain to be characterized.